Catabolism of Alkylphenols in Rhodococcus via a Meta-Cleavage Pathway Associated With Genomic Islands - Levy-Booth, David J.; Fetherolf, Morgan M.; Stewart, Gordon R.; Liu, Jie; Eltis, Lindsay D.; Mohn, William W. (Frontiers in Microbiology, 2019)
The bacterial catabolism of aromatic compounds has considerable promise to convert lignin depolymerization products to commercial chemicals. Alkylphenols are a key class of depolymerization products whose catabolism is not well elucidated. We isolated Rhodococcus rhodochrous EP4 on 4-ethylphenol and applied genomic and transcriptomic approaches to elucidate alkylphenol catabolism in EP4 and Rhodococcus jostii RHA1. RNA-Seq and RT-qPCR revealed a pathway encoded by the aphABCDEFGHIQRS genes that degrades 4-ethylphenol via the meta-cleavage of 4-ethylcatechol. This process was initiated by a two-component alkylphenol hydroxylase, encoded by the aphAB genes, which were up-regulated ~3,000-fold. Purified AphAB from EP4 had highest specific activity for 4-ethylphenol and 4-propylphenol (~2000 U/mg) but did not detectably transform phenol. Nevertheless, a ΔaphA mutant in RHA1 grew on 4-ethylphenol by compensatory up-regulation of phenol hydroxylase genes (pheA1-3). Deletion of aphC, encoding an extradiol dioxygenase, prevented growth on 4-alkylphenols but not phenol. Disruption of pcaL in the β-ketoadipate pathway prevented growth on phenol but not 4-alkylphenols. Thus, 4-alkylphenols are catabolized exclusively via meta-cleavage in rhodococci while phenol is subject to ortho-cleavage. A putative genomic island encoding aph genes was identified in EP4 and several other rhodococci. Overall, this study identifies a 4-alkylphenol pathway in rhodococci, demonstrates key enzymes involved, and presents evidence that the pathway is encoded in a genomic island. These advances are of particular importance for wide-ranging industrial applications of rhodococci, including upgrading of lignocellulose biomass.